Makna Hari Akhir dalam QS. al-Haqqah Perspektif Semiotika Analitis Charles Sanders Pierce - Zahrotun, Zahrotun (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This writing aims to examine the meaning of the Day of Judgment in Surah Al-Haqqah and analyze the vocabulary within it through the semiotics of Charles Sanders Pierce. Pierce's semiotics divides signs based on their relationship between the representamen and the object into three categories: icon, index, and symbol. Surah Al-Haqqah depicts a horrifying and tense atmosphere for those who are disobedient in this world. The depiction of human deeds, both good and bad, is evident. No creature can hide from Him. This research adopts a qualitative approach. The results of the analysis in this study are as follows: out of the fifty-two verses in Surah Al-Haqqah, there are six quoted icons related to the Day of Judgment. Secondly, there are ten scattered indexical quotes within Surah Al-Haqqah. Thirdly, out of the fifty-two verses in Surah Al-Haqqah, the most frequently found signs in the form of symbols, amounting to seventeen verses.